Digoxin treatment is associated with increased total and cardiovascular mortality in anticoagulated patients with atrial fibrillation. (1st February 2015) - Pastori, Daniele; Farcomeni, Alessio; Bucci, Tommaso; Cangemi, Roberto; Ciacci, Paolo; Vicario, Tommasa; Violi, Francesco; Pignatelli, Pasquale
Abstract: Background: Some evidences suggest that the use of digoxin may be harmful inatrial fibrillation (AF) patients. The aim of the study was to investigate in a "real world" of AF patients receiving vitamin K antagonists (VKAs), the relationship between digoxin use and mortality. Methods: Prospective single-center observational study including 815 consecutive non-valvular AF patients treated with VKAs. Total mortality was the primary outcome of the study. We also performed a sub-analysis considering only cardiovascular (CV) deaths. Time in therapeutic range (TTR) was used for anticoagulation quality. Results: Median follow-up was 33.2 months (2460 person-years); 171 (21.0%) patients were taking digoxin. Compared to those without, patients on digoxin were older (p = 0.007), with a clinical history of HF (p < 0.001) and at higher risk of thromboembolic events (p < 0.001). No difference in TTR between the two groups was registered (p = 0.598). During the follow-up, 85 deaths occurred: 47 CV and 38 non-CV deaths; 35 deaths occurred in digoxin users (20.6%). A significant increased rate of total mortality was observed in digoxin-treated patients (p < 0.001). Multivariable analysis showed that digoxin was associated with total mortality (hazard ratio [HR]: 2.224, p < 0.001) and CV death (HR: 4.686, p < 0.001). A propensity score-matched analysis confirmed that digoxin was associated with total mortality (HR: 2.073, p = 0.0263) and CV death (HR: 4.043, p = 0.004). Conclusions: In AF patients on good anticoagulation control with VKAs, digoxin use was associated with a higher rate of total and CV mortality. Highlights: In this prospective cohort study of anticoagulated AF patients, digoxin use is associated with increased mortality. This association is evident in AF patients with or without heart failure exposed to digoxin. Lacking randomized controlled studies in AF, the use of digoxin should be carefully considered in this setting.